Forensic Monitoring Project Report: Rogatica Exhumations State Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The State Commission on Missing Persons (Bosniak) exhumed 37 sets of remains from 13 sites in the Rogatica area between 1-4 September 1998. One additional set of remains was collected 15 September. The deaths were the result of 1992 fighting in and around Rogatica between Bosniak and Bosnian Serb forces. Place of Exhumation: Rogatica Exhumation Site: Vragolovi, Kramer Selo, Kozadre, Gornje Kukavice, Čadovina, Šljivno, Kopljevići, Pašića Kula, Rakitnica, Mesići Date of Exhumation: 1-4, 15 September 1998 Minimum Number of Exhumed Individuals: 038